PENGARUH MEKANISME CORPORATE GOVERNENCE DAN SPESIALISASI INDUSTRI AUDITOR TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi Empiris Pada Perusahaan BUMN yang terdaftar di Bursa Efek Indonesia pada Tahun 2013-2015) - Syura, Bani; Anugerah, Rita; Julita, Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was examined the influence of Independent Commisaries, Audit Commite, Institutional Ownership, Management Ownership and Auditor Industry Specialization To Financial Statement Integrity. The population in this study are all BUMN Companies listed in Bursa Efek Indonesia in years 2013- 2015. This research is included in quantitative research. The type of data used in this study is secondary data from financial statement of the aforementioned BUMN Companies and data derived from the IDX fact book and Indonesian Capital Market Directory, sampling is done by the method of purposive sampling is the technique of sampling with certain considerations. The total sample in this study are 17 firms. These data were analyzed using multiple regression analysis with SPSS Version 17. The results of this study showed that Independent Commisaries affects Financial Statement Integrity with significant value 0,005, Audit Commite affects Financial Statement Integrity with significant value 0,019, Institutional Ownership affects Financial Statement Integrity with significant value 0,038, Management Ownership affects Financial Statement Integrity with significant value 0,001 and Auditor Industry Specialization affects Financial Statement Integrity with significant value 0,000. So the conclusion of this research is all hypothesis presented acceptable.Keywords : Financial Statement Integrity, Independent Commisaries, Audit Commite, Institutional Ownership, Management Ownership and Auditor Industry Specialization